Design of Horizontal Shell Core Casting Machine for Small and Medium Enterprise in the Automotive Sector - Armansyah; Agus Sudianto; Budhi Martana; Satrio Bagas Damar Handito; Ridwan Bambang Riantio; Raden Pranaya Didva; Ferdyanto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The manufacturing industry plays an important role in a country’s economy because it can produce high-value products and has the opportunity to create jobs for local communities. In this study, the authors designed a horizontal shell core casting machine for small and medium enterprises in the automotive sector with a productivity of 60 seconds per cycle of products is designed based on requirements needed. This shell core casting machine is a device to produce shell core molds used to manufacture automotive components and parts. The design of this device was focused on engineering design in the form of 2-dimensional drawings and computer aided design models in 3-dimensional form. This study was done in collaboration with a local machinery manufacturer in Karawang district in Indonesia. It is expected from these designs will become a reference to manufacture shell core casting machines to support national industrialization impacted on improving the local community’s economy.